COLLABORATIVE GOVERNANCE DALAM PENGEMBANGAN UMKM PUDAK DI KECAMATAN GRESIK KABUPATEN GRESIK - Aqshal Bagoes Avanzar Noegroho; Lukman Arif (Halu Oleo University, 2022)
The study of collaborative governance, especially in the MSME sector, certainly does not only focus on government plans but also relates to the actions and temporary impacts felt by Pudak MSME players in Gresik District, Gresik Regency. Pudak is a traditional food from Gresik that must be developed and preserved in order to compete with modern foods in the community. This article aims to describe and analyze of collaborative governance practice to the development of Pudak MSMEs in Gresik District, Gresik Regency. This research was carried out by conducting observations and interviews at the Gresik District office, Cooperatives, Micro Enterprises, Industry and Trade office of Gresik Regency and Pudak MSME merchant in Gresik District and literature studies. This research uses collaborative governance theory from Emerson, Nabatchi, and Balogh in Retno Sunu Astuti et al (2020) which consists of collaboration dynamics, collaboration actions, and collaboration impact & adaptation. The results showed that Pudak MSME merchant in Gresik District still have not received a significant impact from the collaboration between the Government of Gresik Regency and stakeholders. This was because Pudak MSME merchant in Gresik Regency have never had the opportunity to take part in activities carried out by the Government of Gresik Regency and stakeholders. This is a heavy task for the government so that there needs to be more intense socialization and evaluation of the parties involved in collaboration.